USAHA PENINGKATAN KUALITAS AIR DENGAN VARIASI PENAMBAHAN TAWAS-LEMPUNG KERING “AMPO” PADA LIMBAH DOMESTIK YANG MENGANDUNG DETERJEN - Nilna Amal (Universitas Lambung Mangkurat, 2011)
Detergent is one type of pollutants that found in domestic wastewater disposal, especially produced from laundry activities. Accumulated detergent physically effected to water body causes foaming and high turbidity therefore causes bad smell. Nowadays, there are no many well known research easily and effectively to remove detergent content. This research proposes an easy and moderate process to remove detergent content from domestic effluent with cheap and available materials. It can useful as references to design some unit operation of wastewater treatment for domestic effluent with detergent contents. For this aim, it has chosen a treatment system coagulation flocculation which give alum coagulant and dry clay coagulant aid called “ampo”, thereafter rapid mixing is conducted along 5 minutes, this process continue with sedimentation. This research is conducted in laboratories scale use simulation water thereafter, tried to the real wastewater effluent. Detergent content variable vary from 20 mg/l, 60 mg/l and 100 mg/l then optimum alum dosage is determined. It is used to determine the optimum dosage alum-dry clay “ampo” combination with various detention time variables. Research finding shows linear correlation between initial detergent content with less of it. It means that if the more detergent content used the lower efficiency occur. The detention time also influence in process decreasing of detergent content, 48 hours is the best condition. Optimum condition found at optimum dosage alum 125 mg/l and ampo 25 g/l and the 48 hours detention time which reach 41%.in efficiency.